1986
DOI: 10.1159/000260932
|View full text |Cite
|
Sign up to set email alerts
|

Caries Prevalence and Gingivitis in 5-, 7- and 10-Year-Old Schoolchildren in The Hague between 1969 and 1984

Abstract: In 1969, 1972, 1975, 1978 and 1981 dental examinations have been carried out in The Hague on cohorts of children of kindergartens and elementary schools at the occasion of the start of a long-term dental health education campaign. In 1984 a follow-up part of the cohort examinations was conducted on 5-, 7- and 10-year-old schoolchildren. In 1984 further improvement in dental health of 5-, 7- and 10-year-old children was found. In the 5-year-old children the average d3mfs was 1.61. The average D3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
1
8
1
Order By: Relevance
“…Mild gingivitis had the highest percentage (59.3%) among the school children while moderate gingivitis was (30.3%) in the 12-year-old group, which was higher than that shown among 6-year-old group (20.6%). Although these findings are in agreement with some previous studies, 20,21 it seems different from the findings of Al-Sayyab's study. 28 This might be related to the fact that the mild gingivitis was considered the commonest type in early childhood, whereas the severity of gingival inflammation increases with age.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Mild gingivitis had the highest percentage (59.3%) among the school children while moderate gingivitis was (30.3%) in the 12-year-old group, which was higher than that shown among 6-year-old group (20.6%). Although these findings are in agreement with some previous studies, 20,21 it seems different from the findings of Al-Sayyab's study. 28 This might be related to the fact that the mild gingivitis was considered the commonest type in early childhood, whereas the severity of gingival inflammation increases with age.…”
Section: Discussioncontrasting
confidence: 55%
“…11,12 Different findings have been reported from other parts of the world. [17][18][19][20] These variations may be attributed to differences in methodology and/or age of study samples and may also be related to the socioeconomic condition which reflects genuine differences in oral hygiene practices. Another possible factors might be the culture, food habits, and geographical location that act as independent determinant.…”
Section: Discussionmentioning
confidence: 99%
“…The D?MFS value obtained in this study was in the same range as that found by Truin et al [1986] in a previ ous study of Dutch children of the same age (reported value of 2.18, SD 2.93, n = 222) suggesting that children in the present study are not different with regard to their dental status from a normal Dutch child population.…”
Section: Discussionsupporting
confidence: 88%
“…Between 1978 and 1989 a marked D3MFS reductions amongst 11-year-olds in the three social levels was found. Possible explanations for the observed differences in caries experience between 1984 and 1989 are dis cussed.In the late seventies and early eighties results from epidemiological studies in the US and several Eu ropean industrialized countries dem onstrated that dental caries was declining amongst schoolchildren [Glass, 1981;Anderson et al, 1982;von der Fehr, 1982; Fcjerskov et al, 1982], This was also true in the N eth erlands [Kalsbeck, 1982;Truin et al, 1981Truin et al, , 1985Truin et al, , 1986, The decrease in caries prevalence in Dutch schoolchildren was noticed for the first time in the mid-sev enties, and the decline continued through the 15-year period that followed.Starting in 1969, periodical cross-sectional studies on schoolchildren have been carried out in the city of The Hague. In 1989, the periodical examinations were continued in order to investigate if a further decline in caries prevalance amongst schoolchildren in The Hague could be observed and if differences in caries prevalence between groups of different socio-eco nomic levels (SES) were still present.…”
mentioning
confidence: 99%
“…In cooperation with the Community Department of Statistics of the city The Hague, classification per school was based on the average SES status of the population in the respective area of the city in which the school was situated. The sample consisted of most of the kindergartens and elementary schools earlier selected in the previous years of examinations [Truin et al, 1981[Truin et al, ,1985. Chil dren from ethnic minorities were excluded from the data present ed in this paper.…”
mentioning
confidence: 99%